Integrating carbon accounting into Zimbabwe’s climate mitigation strategy policy and institutional perspective - Munyepwa, Kudakwashe (Goodwood Publishing, 2025)
Purpose: This study investigates the role of carbon accounting in Zimbabwe’s climate change mitigation strategy, focusing on how policy frameworks and institutional capacities affect measurement, reporting, and verification (MRV). It examines the integration of carbon accounting into national climate governance and its influence on achieving Zimbabwe’s Nationally Determined Contributions (NDCs) under the Paris Agreement. Methodology/approach: A qualitative approach was adopted, involving semi-structured interviews with policymakers, Environmental Management Agency regulators, and sustainability officers from key industries. National climate policies, environmental legislation, and carbon audit reports were also analyzed to assess institutional frameworks and reporting practices. Results/findings: Findings reveal that carbon accounting in Zimbabwe remains fragmented and underdeveloped. Limited institutional coordination, capacity gaps, and weak regulatory enforcement impede its effective integration into national planning. Nonetheless, some mining and energy sector entities have initiated voluntary carbon disclosures, motivated by investor and donor expectations. Conclusion: Enhancing coordination and institutional capacity is essential for strengthening carbon accounting practices. Aligning policy intentions with practical implementation is critical to achieving Zimbabwe’s climate objectives. Limitations: The study focused on policy and institutional analyses, excluding quantitative emissions data and project-specific carbon accounting practices. Contribution: This research advances understanding of environmental accountability in Africa by highlighting the policy–institutional link for effective carbon accounting. It provides recommendations for improved governance, standardized reporting, and incentives for carbon disclosures to support Zimbabwe’s climate goals.